Synchronized On/Off Switching of Four Binding Sites for Water in a Molecular Solomon Link. Issue 24 (7th May 2019) - Caprice, Kenji; Pupier, Marion; Bauzá, Antonio; Frontera, Antonio; Cougnon, Fabien B. L.
Abstract: A molecular Solomon link adopts different conformations in acetonitrile (1 ) and in water (2 ). Contrary to expectations, the main driving force of the transformation is not the change in medium polarity, but the cooperative binding of about four molecules of water, forming a tiny droplet in the central cavity of 2 . Mechanistic studies reveal that the four binding sites can simultaneously switch between an inactive state (unable to bind water) and an active state (able to bind water) during the transformation. Spatial and temporal coordination of switching events is commonly observed in biological systems but has been rarely achieved in artificial systems. Here, the concerted activation of the four switchable sites is controlled by the topology of the whole molecule. Abstract : Like in a game of falling dominoes : A molecular Solomon link is presented that possesses four interdependent binding sites that can switch in a concerted way between an inactive and an active state. In the active state, each site binds one molecule of water. Binding of a total of four water molecules to this unusual receptor is highly cooperative.